Atividade da enzima degradadora de insulina no fígado de camundongos obesos submetidos a gastrectomia vertical - Lopes, Luana Emanuelly Sinhori (2021)
Obesity is considered a public health problem, as it contributes to the development of health conditions such as cardiovascular disease, hyperinsulinemia, insulin resistance, and type 2 diabetes mellitus (DM). Aiming at the treatment of obesity and its clinical problems, bariatric surgery appears as an effective and long-lasting alternative for these patients. Among the most frequently performed bariatric procedures, the sleeve gastrectomy (SG) stands out for presenting effects such as normalization of blood glucose, improvement in insulin sensitivity, and fasting insulin concentration. Stabilization of insulinemia occurs through a reduction in insulin secretion and/or an increase in its clearance. Insulin clearance is performed by the insulin-degrading enzyme (IDE), mainly in the liver. However, changes in insulin clearance after SG are not fully elucidated. Thus, the present study aimed to verify whether there is a reduction in insulinemia in obese mice after SG and whether this reduction is due to an increase in insulin clearance in the liver. For this purpose, male mice of the C57BL/6 lineage were used, initially separated into a Control group (CTL, n=9) that received a standard diet, and a High-fat Diet group (DH, n=18) that received a high-fat diet. At 14 weeks of life, the animals in the DH group were subdivided into a High-fat diet-false-operated Group (DH-FO, n=9) which underwent a false operation, and the High-fat diet-sleeve gastrectomy Group (DH-GV, n= 9) submitted to sleeve gastrectomy. After completing 20 weeks, the animals were weighed and measured, and fasting blood glucose was measured. Subsequently, blood was collected for plasma insulin and C-peptide dosages. Furthermore, they were collected from the liver to assess the activity of the IDE enzyme. After the induction of obesity, the body weight, insulin, and glycemia of animals in the DH group were higher compared to the CTL, showing the efficiency of the high-fat diet in increasing weight gain. After bariatric procedures, animals in the DH-GV group showed reduced body weight, stabilization of fasting glucose, improved glucose tolerance, and insulin resistance, compared to animals in the DH-FO group. Fasting insulinemia in DH-GV animals was lower, compared to DH-FO animals, and equal to CTL. Fed insulinemia in DH-GV animals was lower, compared to DH-FO animals, and higher, compared to CTL. The concentration of C-peptide in the fasting and fed state of the DH-GV animals was lower, compared to the DH-FO and CTL group. The C-peptide/insulin ratio, both in the fasting state and in the fed state of the DH-GV animals, was higher, compared to the DH-FO animals, and lower, compared to the CTL group. The IDE activity was similar between the animals of the DH-FO and DH-GV groups and lower than that of the CTL. In conclusion, SG was effective in reducing body weight, stabilizing fasting glycemia and insulinemia; increasing insulin clearance without changing this enzyme’s activity.